2016
DOI: 10.1111/jfb.13064
|View full text |Cite
|
Sign up to set email alerts
|

Aversive responses of captive sandbar sharks Carcharhinus plumbeus to strong magnetic fields

Abstract: This experimental study focused on the possible deterrent effect of permanent magnets on adult sandbar sharks Carcharhinus plumbeus. Results showed that the presence of a magnetic field significantly reduced the number of approaches of conditioned C. plumbeus towards a target indicating that adult C. plumbeus can be deterred by strong magnetic fields. These data, therefore, confirm that the use of magnetic devices to reduce shark by-catch is a promising avenue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Present understanding of the interactions between EMFs and marine animals has benefited from laboratory experiments and field studies using surrogate cables, largely with benthic fish and invertebrates [49][50][51]. However, significant gaps remain in understanding how pelagic species (e.g., sharks, marine mammals, fish) may react to dynamic cables suspended in the water column [52].…”
Section: Risk To Animals From Electromagnetic Fields (Emfs) Emitted By Mre Cablesmentioning
confidence: 99%
“…Present understanding of the interactions between EMFs and marine animals has benefited from laboratory experiments and field studies using surrogate cables, largely with benthic fish and invertebrates [49][50][51]. However, significant gaps remain in understanding how pelagic species (e.g., sharks, marine mammals, fish) may react to dynamic cables suspended in the water column [52].…”
Section: Risk To Animals From Electromagnetic Fields (Emfs) Emitted By Mre Cablesmentioning
confidence: 99%
“…Similarly, strong permanent magnets have been used as sources of aversive stimuli to induce avoidance behaviours in elasmobranchs, including the southern stingray Hypanus americanus (Hildebrand & Schroeder 1928) (O'Connell et al, ), Atlantic sharpnose, Rhizoprionodon terraenovae (Richardson 1837) and M. canis (O'Connell et al, ), great hammerhead shark Sphyrna mokarran (Rüppell 1837) (O'Connell et al, ), white shark Carcharodon carcharias (L. 1758) (O'Connell et al, ), lemon shark Negaprion brevirostris (Poey 1868) (O'Connell et al, , ), C. leucas (O'Connell et al, ), S. canicula and R. clavata , (Smith & O'Connell, ), C. plumbeus (Siegenthaler et al, ) and the blind shark Brachaelurus waddi (Bloch & Schneider 1801) (Richards et al, ). However, it is unclear whether the repulsive effects reported were because the test subjects responded directly to magnetic stimuli or to induced electrical artefacts.…”
Section: Behaviourmentioning
confidence: 99%
“…Jordan et al (2011) described that the presence of conspecifics may invoke competitive feeding behaviours which override any deterrent effect of magnets and that the magnetic field may actually attract individuals in these situations. Smith and O'Connell (2014) and Siegenthaler et al (2016) both conducted controlled lab experiments using neodymium-based rare earth magnets to successfully deter foraging attempts of three elasmobranch species, conflicting with a later lab study on sand tiger sharks (Carcharias taurus) that showed no effect (Polpetta et al 2021). Field trials of rare earth magnets have resulted in mixed responses of Australian swellshark (Cephaloscyllium laticeps) in trap fisheries (Westlake et al 2018) and increased bycatch of blue shark (Prionace glauca) in longlines (Porsmoguer et al 2015).…”
Section: Electrosensorymentioning
confidence: 99%